External Validation of BMT-i Computerized Test Battery for Diagnosis of Learning Disabilities - Billard, Catherine; Jung, Camille; Munnich, Arnold; Gassama, Sahawanatou; Touzin, Monique; Mirassou, Anne; Willig, Thiébaut-Noël (Frontiers in Pediatrics, 2021)
Abstract Background: Learning disabilities (LDs) are a major public health issue, affecting cognitive functions and academic performance for 8% of children. If LDs are not detected early and addressed through appropriate interventions, they have a heavy impact on these children in the social, educational, and professional spheres, at great cost to society. The BMT-i (Batterie Modulable de Tests informatisée, or “computerized Adaptable Test Battery”) enables fast, easy, reliable assessments for each cognitive domain. It has previously been validated in children ages 4 to 13 who had no prior complaints. The present study demonstrates the sensitivity of the BMT-i, relative to reference test batteries, for 191 children with cognitive difficulties. Materials and Methods: These 191 subjects were included in the study by the 14 pediatricians treating them for complaints in five cognitive domains: written language (60 [cases]); mathematical cognition (40); oral language (60); handwriting, drawing, and visuospatial construction (45); and attention and executive functioning (45). In accordance with a predefined protocol, the children were administered BMT-i tests first, by their pediatricians, and reference tests later, by specialists to whom the BMT-i test results were not disclosed. Comparison of BMT-i and reference test results made it possible to evaluate sensitivity and agreement between tests. Results: For each of the five domains, the BMT-i was very sensitive (0.91–1), and normal BMT-i results were highly predictive of normal results for specialized reference tests (negative likelihood ratio [LR−]: 0–0.16). There was close agreement between BMT-i and reference tests in all domains except attention and executive functioning, for which only moderate agreement was observed. Conclusion: The BMT-i offers rapid, reliable, simple computerized assessments whose sensitivity and agreement with reference test batteries make it a suitable first-line instrument for LD screening in children 4 to 13 years old.